2001
DOI: 10.1253/jcj.65.788
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Dysfunction in Chronic Nonvalvular Atrial Fibrillation is Significantly Associated With an Elevated Level of Brain Natriuretic Peptide and a Prothrombotic State.

Abstract: trial fibrillation (AF) is associated with serious complications such as arterial thromboembolism, 1 and in patients with nonvalvular AF (NVAF) left atrial appendage (LAA) thrombi are believed to be the source of embolism. 2 In sinus rhythm, the LAA vigorously contracts with a peak emptying flow velocity greater than 50 cm/s, 3 but this is reduced in patients with chronic NVAF. 4,5 Although LAA dysfunction is a significant predictor of thrombus formation, the pathophysiologic mechanisms responsible have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
(40 reference statements)
4
36
0
Order By: Relevance
“…39 Therefore, it is believed that in a patient with AF, BNP is primarily produced in the atria, whereas in a patient with heart failure, natriuretic peptide is mainly released by ventricles. 40,41 Elevated levels of BNP have been correlated with left atrial appendage dysfunction, 42,43 which itself is associated with increased risk for thromboembolic events in AF patients. 14 The prevalence of elevated biomarkers and their association with cardiovascular events in AF patients receiving chronic anticoagulation were studied independently in two clinical trials: Apixaban for the Prevention of Stroke in Subjects with Atrial Fibrillation (ARISTOTLE) and Randomized Evaluation of Long-Term Anticoagulation Therapy (RE-LY).…”
Section: Brain Natriuretic Peptidementioning
confidence: 99%
“…39 Therefore, it is believed that in a patient with AF, BNP is primarily produced in the atria, whereas in a patient with heart failure, natriuretic peptide is mainly released by ventricles. 40,41 Elevated levels of BNP have been correlated with left atrial appendage dysfunction, 42,43 which itself is associated with increased risk for thromboembolic events in AF patients. 14 The prevalence of elevated biomarkers and their association with cardiovascular events in AF patients receiving chronic anticoagulation were studied independently in two clinical trials: Apixaban for the Prevention of Stroke in Subjects with Atrial Fibrillation (ARISTOTLE) and Randomized Evaluation of Long-Term Anticoagulation Therapy (RE-LY).…”
Section: Brain Natriuretic Peptidementioning
confidence: 99%
“…5 Furthermore, the plasma BNP concentration is an independent negative predictor for the LAA peak flow velocity and serves as a determinant of LAA function in nonvalvular AF. 6 In addition, Kim et al showed that the duration of AF is an independent predictor of plasma BNP levels in patients with chronic AF and preserved LV systolic function, due to the influence on the LAA peak flow velocity. 7 In conclusion, LV dysfunction is a determinant of LAA function and therefore increases BNP levels.…”
Section: To the Editormentioning
confidence: 99%
“…7 In conclusion, LV dysfunction is a determinant of LAA function and therefore increases BNP levels. 6 In addition to LV dysfunction, increased plasma BNP levels could be related to rapid progression of LAA dysfunction in patients with AF. 6 Transesophageal echocardiography can be used to identify relationships between LAA peak flow velocities, duration of AF, and plasma BNP levels.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations